2008
DOI: 10.1210/jc.2007-2564
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Adrenocortical Carcinoma with Erlotinib plus Gemcitabine

Abstract: Salvage chemotherapy using erlotinib plus gemcitabine has very limited to no activity in patients with very advanced ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(80 citation statements)
references
References 30 publications
4
73
0
3
Order By: Relevance
“…Our study confirms the disappointing results of salvage therapies in ACC reported in other studies (29,33,34). It further demonstrates that the natural course of ACC is progressive and that spontaneous tumour regressions as described for other tumour entities, e.g.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study confirms the disappointing results of salvage therapies in ACC reported in other studies (29,33,34). It further demonstrates that the natural course of ACC is progressive and that spontaneous tumour regressions as described for other tumour entities, e.g.…”
Section: Discussionsupporting
confidence: 89%
“…Etoposide, doxorubicin and cisplatin plus mitotane as well as streptozotocin plus mitotane were administered in all patients (nine of them within the FIRM-ACT trial). Furthermore, six patients were pretreated with gemcitabine plus erlotinib (29), three with sunitinib and three with radiotherapy and chemoembolization necessary. Five patients had concomitant mitotane, because it was at the discretion of the local physician to continue with mitotane when some clinical benefit was presumed.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In 10 patients with advanced adrenocortical carcinoma, the combination of the EGFR inhibitor erlotinib with gemcitabine did not lead to any objective tumor response, and preliminary similar results were reported for gefitinib. 45,46 During our work-up all cases with no specific staining for EGFR on the TMAs were stained in sections from the corresponding original tissue blocks. Although a majority of cases (n ¼ 41; 63%) remained negative, focal expression of EGFR was observed in the other cases (weak n ¼ 7, moderate n ¼ 11 and strong n ¼ 6), demonstrating the known heterogeneous expression of EGFR that has also been described for other tumor entities.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of combined treatment with erlotinib and gemcitabine as salvage therapy was assessed in the group of patients with progressive ACC after two to four previous systemic therapies. Only one in 10 patients experienced a minor response, whereas eight patients progressed, suggesting that salvage chemotherapy using this regimen has no benefit in patients with very advanced ACC [180].…”
Section: Selected Targeted Therapies In Adrenocortical Cancermentioning
confidence: 99%